Calcium looping performance under extreme oxy-fuel combustion conditions in the calciner. (15th June 2018) - Arias, B.; Diego, M.E.; Méndez, A.; Alonso, M.; Abanades, J.C.
Highlights: Calcium looping with a calciner operated under rich-oxygen conditions has been tested at TRL6. Experiments with a coal thermal input of up to 2.0 MWth and 75 O2 %v in the oxidant were performed. No hot spots were detected in the calciner reactor operated under these conditions. Abstract: Calcium looping (CaL) for post-combustion CO2 capture is an emerging technology that has developed rapidly due to its similarities with existing circulating fluidized bed combustion boilers. This work presents an alternative calciner configuration as it is applied in La Pereda CaL pilot plant, the aim of which is to minimize or altogether eliminate the need to recycle CO2 during the oxy-fuel combustion of coal in the calciner. The strategy underlying this configuration is to reduce the heat demand in the calciner, and hence the energy penalty of the whole CaL system. After undergoing several modifications, the pilot was able to operate under O2 -rich conditions in a series of experiments with a coal thermal input of up to 2.0 MWth in the calciner and 75 O2 %v in the oxidant. No hot spots were detected in the calciner reactor in these conditions due to the thermal ballast effect produced by the circulating solids from the carbonator. This new operation mode in the calciner in no way undermined the performance of the carbonator and CO2 capture efficiencies close to the maximum limit permitted by the equilibrium were achieved during the experimental campaigns. In short, the results of this work indicate that it may well be possible to operate the calciner of a CaL system using pure oxygen.